Gli aspetti metaforici e storici della peste nella letteratura greca antica: Omero, Sofocle, Tucidide - Czerwińska, Jadwiga (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
The plague as a terrifying phenomenon affecting people has been a constant toposin literature since antiquity. Its nature and the mysterious way in which it appearedattracted the attention and imagination of poets, who explained it as a punishment sentby the gods for the failings of people who broke the divine commandments and norms.This is how it was depicted by Homer, followed by the tragedians. However, we owe oneof the most poignant images of this disease to Thucydides, the Greek historian of the 5thcentury BC. He created a faithful and at the same time shocking description of it, because itexposed the most shameful aspects of anthopeia physis, human nature. The signalled issueswill become the subject of description in this article.